2018
DOI: 10.1093/jnen/nly048
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Study of Long-Term Survivors of Glioblastoma by Gene-Targeted Next-Generation Sequencing

Abstract: Glioblastoma (GBM) is the most common malignant adult primary brain tumor. Despite its high lethality, a small proportion of patients have a relatively long overall survival (OS). Here we report a study of a series of 74 GBM samples from 29 long-term survivors ([LTS] OS ≥36 months) and 45 non-LTS. Using next-generation sequencing, we analyzed genetic alterations in the genes most frequently altered in gliomas. Approximately 20% of LTS had a mutation in the IDH1 or IDH2 (IDH) genes, denoting the relevance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…This was also the case for MGMT mRNA expression [65]. Moreover, an interesting observation is the involvement of alpha thalassemia/mental retardation syndrome X-linked (ATRX) gene in longer survival of glioblastoma patients [6,70]. Using a gene-targeted next-generation sequencing panel, Cantero et al found better prognosis for glioblastoma patients whose tumors present with ATRX or DAXX mutations in the absence of IDH or H3F3A mutations [70].…”
Section: Long-term Glioblastoma Survivorsmentioning
confidence: 91%
See 1 more Smart Citation
“…This was also the case for MGMT mRNA expression [65]. Moreover, an interesting observation is the involvement of alpha thalassemia/mental retardation syndrome X-linked (ATRX) gene in longer survival of glioblastoma patients [6,70]. Using a gene-targeted next-generation sequencing panel, Cantero et al found better prognosis for glioblastoma patients whose tumors present with ATRX or DAXX mutations in the absence of IDH or H3F3A mutations [70].…”
Section: Long-term Glioblastoma Survivorsmentioning
confidence: 91%
“…Moreover, an interesting observation is the involvement of alpha thalassemia/mental retardation syndrome X-linked (ATRX) gene in longer survival of glioblastoma patients [6,70]. Using a gene-targeted next-generation sequencing panel, Cantero et al found better prognosis for glioblastoma patients whose tumors present with ATRX or DAXX mutations in the absence of IDH or H3F3A mutations [70]. Similar findings were published by Chaurasia et al who reported significantly higher OS and progression-free survival (PFS) in glioblastoma patients with alpha thalassemia/mental retardation syndrome X-linked (ATRX) and IDH1 mutant protein expression (ATRX-and IDH+, respectively) [6].…”
Section: Long-term Glioblastoma Survivorsmentioning
confidence: 99%
“…Therefore, we sought to identify other variables that could potentially predict clinical outcomes prior to vaccination initiation. Because 3-y survival is a very common cutoff to define LTS in GBM clinical studies, [8][9][10][11] we first stratified patients into long-term survivors (LTS, >3 y) and short-term survivors (STS, ≤3 y).…”
Section: Baseline Clinical Characteristics Of Long-and Short-term Surmentioning
confidence: 99%
“…We used a custom Ampliseq (PCR-based) gene-targeted NGS panel that analyze 30 genes that were previously demonstrated to be frequently mutated in gliomas 12 . DNA from formalinfixed paraffin-embedded (FFPE) tumor tissues was extracted using the QIAamp DNA FFPE Tissue Kit (Qiagen).…”
Section: Molecular Characterization Of the Tumorsmentioning
confidence: 99%